Borohidreto complexos de cobre (I) contendo difosfinas. Caracterização espectroscópica e comportamento térmico - Haddad, Paula S. [UNESP]; Mauro, Antonio Eduardo [UNESP]; Frem, Regina C.G. [UNESP] (FapUNIFESP (SciELO), 2001)
Tetrahydroborate complexes of copper (I) with bidentate phosphines, [Cu(η 2-BH 4)(dppm)] (1), [Cu(η 2-BH 4)(dppe)] (2), [Cu(η 2-BH 4)(cis-dppet)] (3) and [Cu(η 2-BH 4)(dppb)] (4) (dppm = bis(diphenylphosphino)methane; dppe = 1,2-bis(diphenylphosphino) ethane; cis-dppet = 1,2-cis(diphenylphosphino)ethene; dppb = 1,4-bis(diphenylphosphino)butane) were prepared and characterized by elemental analysis, infrared spectroscopy, NMR and thermogravimetric analysis. The IR data for 1-4 showed bands typical of a bidentate coordination of BH 4 group to the copper atom and the 31P{ 1H} NMR spectra indicated that the phosphorous atoms are chelating the metal centre. The thermal behavior of the compounds was investigated and suggested that their thermal stability is influenced by the phosphines. Their thermal stability decreased as follows: [Cu(η 2-BH 4)(dppe)] (2) > [Cu(η 2-BH 4)(dppm)] (1) > [Cu(η 2-BH 4)(dppb)] (4) > [Cu(η 2-BH 4)(cis-dppet)] (3). According to thermal analysis and X-ray diffraction patterns all compounds decomposed giving Cu(BO 2) 2, CuO, CuO 2 and Cu as final products.
Tetrahydroborate complexes of copper (I) with diphosphines. Spectroscopic characterization and thermal behavior
Keywords: Bidentate phosphines; Copper (I); Tetrahydroborate